2021
DOI: 10.3390/foods10061174
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste Biorefinery: Pathway towards Circular Bioeconomy

Abstract: Food waste biorefineries for the production of biofuels, platform chemicals and other bio-based materials can significantly reduce a huge environmental burden and provide sustainable resources for the production of chemicals and materials. This will significantly contribute to the transition of the linear based economy to a more circular economy. A variety of chemicals, biofuels and materials can be produced from food waste by the integrated biorefinery approach. This enhances the bioeconomy and helps toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 143 publications
0
34
0
Order By: Relevance
“…Acetogenic bacteria also produce H 2 as a byproduct. Tsegaye et al (2021) reported the biological synthesis of H 2 from a variety of wastes. Process parameters such as the type or origin of inoculum, pretreatment strategy, pH, co-digestion, reactor configuration, and temperature influence H 2 production through AD directly (Mohan et al, 2019).…”
Section: Biohydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetogenic bacteria also produce H 2 as a byproduct. Tsegaye et al (2021) reported the biological synthesis of H 2 from a variety of wastes. Process parameters such as the type or origin of inoculum, pretreatment strategy, pH, co-digestion, reactor configuration, and temperature influence H 2 production through AD directly (Mohan et al, 2019).…”
Section: Biohydrogenmentioning
confidence: 99%
“…Setting up of community-level composting facilities to transform FW into a nutrient-rich biofertiliser could be considered a cost-effective way to reduce ecological consequences and ensure sustainable development. Microbial pretreatment of FW with the lipolytic and thermophilic Brevibacillus borstelensis SH168 enhanced the biofertiliser quality with increased nitrogen (2.01-2.10%) and ash (24.94-29.21%) contents (Tsegaye et al, 2021). Thermal hydrolysis of FW could yield safe liquid organic fertiliser by reducing its bio-and phyto-toxicities (Gao et al, 2021).…”
Section: Biofertilisermentioning
confidence: 99%
“…In this scenario, agro-wastes processing for recovering bioactive compounds or developing innovative and green bio-based materials is in full agreement with the motto of the circular economy. This considers the reuse and recycling of residues as a starting point for building a network of industrial strategies, leading to the definition of a mechanism for a sustainable future [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of FW is inevitable but can be avoided and reduced by creating methods which can valorize FW toward a sustainable bioeconomy, accomplishing the United Nations sustainable development goal of 2030 to reduce by food waste production by 50%. In 2019, there was a global generation of 931 million tons of food waste, according to the UN Environment Program Food Waste Index report [2].…”
Section: Introductionmentioning
confidence: 99%
“…Biorefinery is a concept in which FW is exploited to its integral potential and converted into value-added bioactive molecules and ingredients such as carbohydrates, proteins and bio-based enzymes, biofuels, biopolymers, bio-based molecules and materials [3]. This concept enters in the circular bioeconomy approach which encompasses the production of value-added products in a sustainable and integrated manner, while generating zero waste and reducing/eliminating waste management problems and related costs by employing green methodologies and technologies for FW valorization and recycling [2,4].…”
Section: Introductionmentioning
confidence: 99%